Peran Dinas Pendidikan Dan Kebudayaan Dalam Upaya Pelestarian Cagar Budaya Di Kotawaringin Barat - jamri; syamsuri, syamsuri; Eddy, Lion (Center of Language and Cultural Studies, 2022)
This study discusses the role of the Office of Education and Culture of Kotawaringin Barat Regency in efforts to preserve Cultural Heritage in Kotawaringin Barat Regency. The cultural heritage discussed in this study is the Kyai Gede Mosque, Astana Al-Nursari, and the Prince Mangkubumi Palace. This study aims to describe and analyze the roles and efforts of the Education and Culture Office of Kotawaringin Barat Regency and the factors that influence the preservation of Cultural Heritage in Kotawaringin Barat Regency. The method used in this research is a qualitative descriptive approach. Informants in this study as many as 8 people including researchers. Data collection techniques in this study are observation, interviews, and documentation. The researcher's technique uses qualitative data, namely all materials, information, and facts that cannot be measured and calculated systematically because their form is verbal information (sentences and data). With this technique, the researcher only collects data, information, facts facts, statements in the form of sentences and data from problems that researchers consider important and support in terms of data collection from the relevant agencies at the Office of Education and Culture of Kotawaringin Barat Regency. The results of this study indicate that the role of the Office of Education and Culture in managing Cultural Heritage acts as a regulator is to prepare directions to balance the implementation of cultural heritage preservation through regulations, as a dynamist is to mobilize community participation both individuals and institutions related to the preservation of cultural heritage, and the facilitator is the government is engaged in the field of assistance through training, education and skills improvement as well as in the field of funding and capital.